O atendimento das crianças com deficiência mental: visão das mães e dos profissionais do CAPSi de Itu-SP - Lupo, Ana Paula Rodrigues (2017)
Introduction: The incidence of mental health changes has increased considerably and the consequences of this tend to be tragic if the subject is not very well taken care of. In Brazil, the psychiatric reform is in full development. Children's Psychosocial Care Centers (CAPSi) are structures responsible for organizing the mental health services network in their territory, providing support and supervising mental health care in the basic health network. In Itu-SP there is a single CAPSi in the municipality. It was created in 2011 and has been showing a constant increase in the number of visits. We carried out a study about the perception of the care of both the employees and the mothers of the children served in this service.Objectives:1. To analyze how the professionals of the Child Psychosocial Care Center (CAPSi) "NeideBeneditaZacariasTasca" of Itu /SP perceive the needs and their collaboration in the education of mothers of children with mental disabilities; 2. Analyze how mothers with mentally handicapped children perceive the education they received from CAPSi professionals. Methodology: This is a descriptive, exploratory research with a qualitative approach, which presents as a theoretical reference the Discourse of the Collective Subject and was carried out at the NeideBeneditaZacariasTasca Children's Psychosocial Care Center "(CAPSi) de Itu / SP. The effectiveness of a group spontaneously created by the mothers of the children also researched. All employees and all mothers were invited and accepted to participate in the study 10 of the 13 employees and 30 of the 103 mothers.Results: For Employees, forty percent of them do not feel fully safe at work and suggest that they should be better trained; Eighty percent believe that their guidelines are ineffective and justify that the effectiveness of the guidelines depends on other factors and suggest that the demand for children is reduced. Regarding the conclusion of the mothers' interviews, all the mothers interviewed had some difficulty in getting to the service; Seventy percent believe that CAPSi is the best place to treat serious children; Sixty percent do not feel safe in relation to the guidelines received; Forty percent feel safe, but assigns this security to the group of mothers; All mothers suggest decreased demand in Itu'sCAPSi and establishment of other referral centers. Conclusions: Although more studies are needed to confirm the complaints pointed out in our research, the current survey may contribute to measures being taken to improve care in the ItuCAPSi